(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article provides views on the costs that constitute the cost of production, work and services in economic entities specializing in production and service provision in our country. It also covers the grouping of costs in accordance with the Regulation approved by the Cabinet of Ministers of the Republic of Uzbekistan by Resolution No. 54 dated February 5, 1999. In addition, the most common analytical methods using data on variable and fixed costs are described.